The effects of pastoralism and protection on the density and distribution of carnivores and their prey in the Mara ecosystem of Kenya - Ogutu, J.; Bhola, N.; Reid, Robin S. (Wiley, 2005)
The overlap of large carnivores, livestock and people can engender conflicts that often threaten the future viability of carnivore populations in the pastoral systems of Africa. A playback survey of lions Panthera leo, spotted hyenas Crocuta crocuta and black-backed jackals Canis mesomelas and a transect count of wild herbivores was conducted in the Maasai Mara National Reserve and adjoining pastoral ranches to assess the effect of pastoralism and protection on the density and distribution of carnivores in June 2003. Reliability of the prey counts depended on an assumption of similar observability between the protected and pastoral areas, which we assessed using distance sampling in November 2003 and computer simulations and determined to be similar. Estimates of wild prey biomass density was 2.6 times higher in the ranches (14212 kg/km2) than in the reserve (5472 kg/km2) during this wet season count. Apparent hyena density estimates were 1.3 times higher in the ranches (0.561 hyenas/km2) than in the reserve (0.404 hyenas/km2), in correspondence with the regional pattern of prey density. This distribution of hyenas is biased towards the reserve, if it is dependent on prey density. Estimates of apparent jackal density were similar in both areas whereas lion density was anomalously 8.0 times lower in the ranches (0.046 lions/km2) than in the reserve (0.369 lions/km2). Lion and hyena densities and prey biomass did not differ between June 1991 (5172.273 kg/km2) and June 2003 (5472 kg/km2) in the reserve, but jackal density increased in the same period. Lions never responded to playbacks in the ranches, so the potential shift in lion behavioural response for different land use zones is another potential explanation for the patterns found here. We think a real shift in lion populations is a better explanation than a behavioural change in relation to playbacks based on additional data from independent systematic and intensive censuses and playback surveys conducted in the ranches. Lion populations in the pastoral ranches seemed headed for extinction, probably owing to conflicts with pastoralism, necessitating urgent conservation interventions that integrate pastoral economic welfare with large carnivore conservation goals to foster long-term viability of lion populations in the pastoral systems.